2021
DOI: 10.7146/sjsep.v3i.125734
|View full text |Cite
|
Sign up to set email alerts
|

Maintaining dual career balance: A scenario perspective on Swedish university student-athletes’ experiences and coping

Abstract: A dual career (DC) scenario perspective was introduced in the Erasmus+ Sports project “Gold in education and elite sport” (GEES) and is characterized by integration of student-athletes’ athletic and non-athletic demands into difficult situations or periods (i.e., scenarios) requiring coping efforts. In this study we consider balance as the primary challenge for student-athletes and set out to identify DC scenarios that influenced university student-athletes’ optimal DC balance, and the factors involved in copi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…This is demonstrated through the athlete's ability to complete school assignments on time, actively participate in the learning process in class, and give the best effort in taking exams in academic classes. The study habits of student-athletes reflect a balancing act between the demands of academic life and a commitment to excellence in sports (Linnér et al, 2021). One key aspect of a studentathlete's study habits is careful time management (Coffey & Davis, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This is demonstrated through the athlete's ability to complete school assignments on time, actively participate in the learning process in class, and give the best effort in taking exams in academic classes. The study habits of student-athletes reflect a balancing act between the demands of academic life and a commitment to excellence in sports (Linnér et al, 2021). One key aspect of a studentathlete's study habits is careful time management (Coffey & Davis, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The differences in income might be explained by the fact that the typical sports of the two clusters differ in popularity and, as a result, in money involved. 48 Ice hockey and alpine skiing are likely to receive high media attention, television money and in return, more lucrative sponsorships compared to sports like rowing. However, the similar amount of hours invested in sport and performance level suggest that both clusters do not differ much in their training regime and are competing at the highest level of their respective sports.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the experienced life situation, challenges, and demands faced by student dual career athletes and working dual career athletes are not identical. 48,49 Students may experience pressure to complete their program in the designated period of study, worry about tests being too difficult, or feel stressed about poor grades. 50 As a result, combining the sport career and secondary occupation has been found to be associated with impaired sleep, 51 poor physical health outcomes, 52 and either academic dropout 50 or athletic disengagement.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the high demands placed on the athlete when trying to combine sports and education can cause stressful study situations, which in turn may result in psychological stress, overtraining and injuries ( Gustafsson et al, 2008 ; O’Neill et al, 2013 ; Sisjord and Sorensen, 2018 ; Sorkkila et al, 2020 ). Harrison et al (2022) and Linnér et al (2021) have also shown that the higher the level of education, the more challenging it becomes for student athletes to combine studies with elite preparatory training, and that student-athletes need coping strategies and support to get optimal dual career balance.…”
Section: Introductionmentioning
confidence: 99%